Methods to measure and classify employment in the agri-food system in Africa south of the Sahara - CGIAR Research Program on Policies, Institutions, and Markets (2019)
A new survey module was developed in 2019 following an analysis of gaps in existing data. This module was piloted in household surveys in six countries (Ghana, Malawi, Nepal, Niger, Tanzania, Uganda).